The usefulness of neuronavigation in functional hemispherectomy - Meneses,Murilo Sousa de (2011)
Catastrophic epileptic encephalopathies in children comprise devastating conditions that features cerebral dysfunction in association with refractory epileptic seizures. The diagnosis is based on the clinical findings, on magnetic resonance imaging (MRI) of the brain and on electroencephalographic findings. For these conditions, surgery remains essential for attaining seizure control. We report two cases of 5-year-old girls. The first one had a diagnosis of Rasmussens syndrome. The second one had a large porencephalic cyst secondary to perinatal cerebral ischemia. Despite trials of anticonvulsants, both patients deteriorated, and a functional hemispherectomy guided by neuronavigation was indicated and performed, with low morbidity and excellent seizure control. The neuronavigation proved to be a valuable guidance tool in performing the functional hemispherectomy, making the disconnections more accurate, and thus decreasing the surgical time and blood loss.